Analysis on evolution of international agricultural trade dependence network from perspective of vulnerability - Wang, Yue; Zhang, Linchen (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe vulnerability of transnational supply of agricultural products has become one of key factors affecting food security at the global scale.MethodsThis study applies the social network analysis method for systematic exploration of the evolution of the international agricultural trade dependence network (TDN) from the perspective of vulnerability. First, agricultural industries that are highly vulnerable in international trade are identified. Then, a network visualization model is constructed for systematic analysis of the evolution of topological structure of the global TDN of highly vulnerable agricultural products. Finally, a temporal exponential random graph model (TERGM) and its separated formation model and dissolution (persistence) model (STERGM) are established for quantitative assessment of the impact of abrupt changes in the economic and trade environment on the TDN of highly vulnerable agricultural products in the period 2018–2020.Results and discussionThe research results show that the highly vulnerable industries in the international agricultural trade are distributed in a wide range, concentrating mainly in meat, animal and vegetable oils, fish and other aquatic products, fruits and nuts, and cereal products, and most of the products in each category is mainly supplied by only a handful of countries. The TDN of highly vulnerable agricultural products exhibits a “polycentric” development trend, that is, shifting from the network structure with a single dominant central node (USA) toward the one with multiple central nodes (USA, Malaysia, Indonesia, Brazil, the Netherlands, etc.). During the period 2018–2020, when bilateral trade frictions intensified and the COVID-19 pandemic raged, the abrupt changes in the economic and trade environment led to significant enhancement in the dependence relations in the international trade of highly vulnerable agricultural products. Such abrupt changes not only induce the trade transfer effect and promote the formation of new trade dependence relations among countries, but also increase the probability of maintaining the existing trade dependence relations. These results can provide practical guidance for preventing and mitigating transnational supply crisis and building a more secure global food guarantee system.